Problems of the Personal Adaptation of Students - Pociūtė, Birutė (Acta Paedagogica Vilnensia, 1991)
Student success is determined by a number of factors, but the main one is the adequate adaptation within the institution of higher education. It may be complicated by personal problems of the students. This article, based on the survey of 1200 students at Vilnius University, has identified the following key issues: learning difficulties, interpersonal relationships, problems and conflicts in the academic group, sexual and existential problems. It was found that the most common problem is a learning difficulty, lead to external factors, e.g., irrational learning loads, lack of learning aids, etc. Equally important are the internal factors, e.g., insufficiently developed controlled attention, perception, language skills, etc., and personal qualities, character traits. Passivity, lability, introversion might enhance the intensity of the manifestation of personal problems or be the cause of problems, and such features as activeness, rationality, stability, on the contrary, can help to successfully tackle these problems. However, it should be noted that even these features, when excessively pronounced, may cause personal problems, internal contradictions. The article also discusses some of the ways to solve students’ personal problems.